Answer

Verified

372k+ views

**Hint:**The given problem is pretty easy and you can solve it in a few steps. Here, you can use the concept of limits and you will let a condition that when x=a, then assume the form as$\dfrac{0}{0}$. So, let’s see how we can solve the given problem.

**Step-By-Step Solution:**

The given problem statement is we need to evaluate$\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{(2+x)}^{5/2}}-{{(a+2)}^{5/2}}}{x-a}$.

Firstly, when x=a, the expression $\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{(2+x)}^{5/2}}-{{(a+2)}^{5/2}}}{x-a}$ assumes the form as$\dfrac{0}{0}$.

So, we will let$Z=\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{(2+x)}^{5/2}}-{{(a+2)}^{5/2}}}{x-a}$.

If we use the formula$\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{n}^{a}}-{{a}^{n}}}{n-a}=n{{a}^{n-1}}$, then also Z will not show the form$\dfrac{0}{0}$as mentioned.

So, we need to simplify, that means,

Now, we will add 2 in the denominator, but we will not change the denominator so we will subtract 2 also, that means, we get,

$\Rightarrow Z=\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{(2+x)}^{5/2}}-{{(a+2)}^{5/2}}}{2+x-(a+2)}$

Now, we will let 2+x=y and a+2=k, as$x\to a;y\to k$, we get,

$\Rightarrow Z=\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{y}^{5/2}}-{{k}^{5/2}}}{y-k}$

Now, we will use the formula$\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{n}^{a}}-{{a}^{n}}}{n-a}=n{{a}^{n-1}}$, we get,

$\Rightarrow Z=\dfrac{5}{2}{{k}^{\dfrac{5}{2}-1}}$

$\Rightarrow Z=\dfrac{5}{2}{{k}^{\dfrac{3}{2}}}$

Now, we will place the value of k in the above equation, we get,

$\Rightarrow Z=\dfrac{5}{2}{{(a+2)}^{\dfrac{3}{2}}}$

**Therefore, after evaluation of$\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{(2+x)}^{5/2}}-{{(a+2)}^{5/2}}}{x-a}$, we get, $\dfrac{5}{2}{{(a+2)}^{\dfrac{3}{2}}}$.**

**Note:**

You just need to note for the evaluation for the above question we need to check if it is in the form of $\dfrac{0}{0}$, if it is not then we will continue to simplify. Here, in this question we used the formula $\underset{x\to a}{\mathop{\lim }}\,\dfrac{{{n}^{a}}-{{a}^{n}}}{n-a}=n{{a}^{n-1}}$ in the simplification.

Recently Updated Pages

The base of a right prism is a pentagon whose sides class 10 maths CBSE

A die is thrown Find the probability that the number class 10 maths CBSE

A mans age is six times the age of his son In six years class 10 maths CBSE

A started a business with Rs 21000 and is joined afterwards class 10 maths CBSE

Aasifbhai bought a refrigerator at Rs 10000 After some class 10 maths CBSE

Give a brief history of the mathematician Pythagoras class 10 maths CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Name 10 Living and Non living things class 9 biology CBSE

Select the word that is correctly spelled a Twelveth class 10 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE

Write the 6 fundamental rights of India and explain in detail